Increased Triangular and Quadrilateral Mathematics Learning Outcomes of Class IV Students Through Learning Cycle Learning Models in 200503 Public Elementary Schools - Ali Rachmad Hasibuan (International Journal of Theory and Application in Elementary and Secondary School Education, 2019)
This study aims to Improve Student Learning Outcomes in Triangular Material and Quadrilateral Class IV 200503 Public Elementary School Education with 30 students. The findings of this study are as follows: (1) The average value of students' mathematics learning in Triangular and Quadrilateral material before the Learning Learning Cycle model is applied in Class IV 200503 Public Elementary School Education is 30%. Based on the average value, it can be said that the student learning outcomes before the application of the Learning Cycle learning model in class IV SD Negeri 200503 Pijorkoling is relatively low. After the Learning Cycle learning model was applied in the material Triangle and Quadrilateral, the percentage value of student learning completeness is 60% at the end of the cycle I.Ã‚Â  At the end of the second cycle the average class value with the percentage of student mastery 93.33%, (2) Application of learning models Learning Cycle on Triangle and Quadrilateral methods can attract students' attention, (3) there is an increase in student learning outcomes after the application of Learning Cycle learning models in Triangle and Quadrangular material in class IV 200503 Public Elementary School, therefore learning Learning Cycle models can improve learning outcomes Specifically Mathematics in Triangle and Quadrilateral Material of students in Class IV SD Negeri 200503 Education.